2022
DOI: 10.1055/a-2003-8789
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Free Muscle Flaps versus Free Fasciocutaneous Flaps for Lower Limb Reconstruction following Trauma: A Systematic Review and Meta-Analysis

Abstract: Background: Free flap reconstruction of the lower limb following trauma often suffers higher complication rates than other areas of the body. The choice of muscle or fasciocutaneous free flap is an area of active debate. Methods: A systematic review of EMBASE, MEDLINE, Pubmed, and Cochrane register from inception to January 10, 2022 was performed. Articles were assessed using the methodological index for non-randomized studies (MINORS) instrument. The primary outcome was to assess and compare the major surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 79 publications
(401 reference statements)
1
12
0
1
Order By: Relevance
“…This is supported by a recent metaanalysis suggesting no difference in complication rates between muscle and fasciocutaneous flaps used for lower extremity reconstruction. 13 Our results demonstrate that the surgical approach to secondary bone grafting does not influence complications, but instead supports the individual surgeon's decision-making as to the best approach. In some cases, secondary surgery is anticipated, and this can influence the choice of flap used in primary soft tissue reconstruction.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This is supported by a recent metaanalysis suggesting no difference in complication rates between muscle and fasciocutaneous flaps used for lower extremity reconstruction. 13 Our results demonstrate that the surgical approach to secondary bone grafting does not influence complications, but instead supports the individual surgeon's decision-making as to the best approach. In some cases, secondary surgery is anticipated, and this can influence the choice of flap used in primary soft tissue reconstruction.…”
Section: Discussionsupporting
confidence: 55%
“…This is supported by a recent meta-analysis suggesting no difference in complication rates between muscle and fasciocutaneous flaps used for lower extremity reconstruction. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2019 systematic review, Bezstarosti et al [ 66 ] summarized methods to repair the defect of soft tissue, and outcomes showed that free flaps (39%), skin grafts (21%), and rotational flaps (11%) were the more frequently selected strategies. In a recent systematic review and meta-analysis, Dow et al [ 101 ] compared the efficacy of free muscle flaps with free fasciocutaneous flaps for reconstruction defects in the lower limbs following trauma. Outcomes showed similar efficacy regarding the incidences of total flap failure, reoperation, and limb salvage between the two methods.…”
Section: Treatmentmentioning
confidence: 99%
“…19 However, this study consisted of a limited traumatic patient population, and notably did not report on the efficacy of the two flap types in achieving limb salvage, ambulation, or osteomyelitis recurrence rates. Additional studies looking at the traumatic patient population showed that there were no significant differences in between muscle and fasciocutaneous free flaps.. 14,20 In contrast to the chronic wound population, patients with traumatic wounds have heightened risks for polymicrobial and recurrent infection that are unique due to mechanism and energy of trauma. 21 Patients with diabetic foot wounds extending to bone or recurrent wounds conferred a 20 times higher risk of osteomyelitis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%